If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + 3) = 7x + 15 Reorder the terms: 4(3 + 2x) = 7x + 15 (3 * 4 + 2x * 4) = 7x + 15 (12 + 8x) = 7x + 15 Reorder the terms: 12 + 8x = 15 + 7x Solving 12 + 8x = 15 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 12 + 8x + -7x = 15 + 7x + -7x Combine like terms: 8x + -7x = 1x 12 + 1x = 15 + 7x + -7x Combine like terms: 7x + -7x = 0 12 + 1x = 15 + 0 12 + 1x = 15 Add '-12' to each side of the equation. 12 + -12 + 1x = 15 + -12 Combine like terms: 12 + -12 = 0 0 + 1x = 15 + -12 1x = 15 + -12 Combine like terms: 15 + -12 = 3 1x = 3 Divide each side by '1'. x = 3 Simplifying x = 3
| 24b+3a=0 | | -q-11=2q+14 | | 8a+11=7+15a | | 3a+24b=0 | | 3+12y=6+18y | | -x+(-x+45)=20 | | 9a+7=2+12a | | 10b+8=15b+4 | | 2(3x+4)=5+1 | | 4a-18b=0 | | 6y-9=7y-1 | | 3-x=2.25 | | 6x^2+24x+30=0 | | 2(3X+5)=5X+5 | | 7z+11=0 | | 132=2l+3w | | 10=3z-8 | | 3x-(6-x)=18 | | 5d-2=2d+6 | | 36x=36+121+1 | | t^2-5t+2fort=-4 | | -x=-0.12 | | f(0)=-2x | | 9+11x=107+x | | 4(3x+2)=11+2 | | 4g+1=5g-1-g | | 8x+1=6x+37 | | 24s-53=49-s | | -2t+5t=-8+4 | | 1.25x+4.25=-7 | | -1.2(z-13)=-2.1(z-16) | | 60(x+24)=80x |